MAYER-ROKITANSKY-KUSTER-HAUSER SYNDROME - Adil, Ruqqayia; Qayyum, Adil (Journal of Ayub Medical College Abbottabad, 2013)
Mayer-Rokitansky-Küster-Hauser Syndrome is a congenital malformation in which there is failure of the Müllerian ducts to develop resulting in absent uterus and fallopian tubes and variable malformations of the vagina. Ultrasonography reveals absence of uterus with normally visualised ovaries. Keywords: Mayer-Rokitansky-Küster-Hauser Syndrome, Müllerian agenesis, Congenital, 46XX